From cervix to multisite: Detection of lower genital tract lesions in a 10-year cross-sectional colposcopy clinic study - Zhongyue Yan; Chenyao Guo; Yao Liu; Jing Li; Quanlong Lu; Ruifang Li; Bo Feng; Chen Wang; Chenju Li; Lei Shi; Tian Feng; Zhilian Wang; et al. (PLoS ONE, 2025)
Objective To evaluate detection rates of multisite lesions (cervical, vaginal, vulvar) among women attending colposcopy clinics. Methods Our cross-sectional study included 20,486 patients between 2014 and 2023 in Shanxi China. Detection rates for cervical, vaginal, and vulvar lesions were retrospectively analyzed across strata by HPV status, cytological diagnosis, and clinical manifestations (vaginal bleeding/discharge). Multinomial logistic regression was applied to calculate odds ratios for high-grade lesions and squamous cell carcinoma (SCC). Results High-risk HPV (hr-HPV) infection was detected in 16,636 of 20,486 women (81.2%), and 9,137 (44.6%) had ASC-US+ cytology. Following cervical lesion detection on histopathology among hr-HPV-positive women (CIN2/3: 19.9%; SCC: 5.3%; AIS/ADC: 0.4%), additional lesions were identified at other anatomical sites: vaginal lesions (VaIN2/3: 3.6%; SCC: 1.1%; AIS/ADC: 0.04%) and vulvar lesions (VIN2/3: 0.4%; SCC: 0.1%) were further identified. Overall, 21.6% of hr-HPV-positive women exhibited high-grade lesions (CIN/VaIN/VIN2/3), with 5.6% demonstrating multi-focal SCC and 0.4% showing AIS/ADC. Stratified analysis revealed that patients even with negative HPV or cytology result still had relative high detection rate of high-grade lesions. Among these HPV-negative women, those reporting vaginal bleeding/discharge carried an elevated risk, with 3.2% having high-grade lesions and 10.5% having SCC. The integrative examination combining hr-HPV, cytology, and vaginal bleeding/discharge identified 3,753 high-grade lesions and 1,154 cancers. Conclusion Integrating the assessment of hr-HPV testing, cytology, and clinical symptoms (e.g., vaginal bleeding or discharge) could help finding more cases of multisite lesions (cervical, vaginal, vulvar). This is especially important for some high-risk women, including those who visit the colposcopy clinics, and more attention should be paid to the multisite examination.